Social functioning and age across affective and non-affective psychoses - Martin, Elizabeth A. (J Nerv Ment Dis, 2015)
Both non-affective and affective psychoses are associated with deficits in social functioning across the course of the illness. However, it is not clear how social functioning varies among diagnostic groups as a function of age. The current study examined the relationship between social functioning and age in schizophrenia (SZ), schizoaffective disorder (SZA), and psychotic bipolar disorder (PBD). We found that individuals with PBD had the highest functioning while individuals with SZ had the poorest. The functioning of individuals with SZA fell in between the other groups. We also found that older ages were associated with poorer functioning. Although there was not a significant diagnostic group by age interaction, visual inspection of our data suggests a subtly steeper trajectory of decline in PBD. These results indicate that a decline in social functioning with may be an important area of unmet need in treatment across psychotic disorders.